Souboj vůle s náklonností: teologické pozadí Kantovy antropologie v "Kritice čistého rozumu" - Navrátilová, Olga (Filosoﬁcký časopis)
In his practical philosophy, Kant reveals the principles of ethics that are based on pure reason and are therefore independent of both empirical anthropology and theology. Nevertheless, it can be argued that his reflections on the nature of morality are conditioned by the concept of humanity as it was shaped by Christian theology, especially in the Lutheran tradition. In this article, the author wants to show that this theological background is not only present in the work Religion within the Boundaries of Mere Reason, which offers Kant’s rational interpretation of the basic Christian theologoumena, but that Kant also builds on it in the Critique of Practical Reason and in his practical philosophy in general. Consequently, neither the concept of radical evil, which represents Kant’s interpretation of the doctrine of original sin, nor the concept of a “revolution in the disposition of the human being,” which is an interpretation of the theological concept of grace, can be understood as a denial of the principles of Kant’s practical philosophy. On the contrary, by elaborating both concepts, Kant makes explicit the implicit theological background of these principles, which does not deprive them, nevertheless, of their philosophical persuasiveness.